Implementasi kebijakan pelayanan angkutan laut perintis di pelabuhan kelas II teluk palu propinsi Sulawesi Tengah - Fahrudin, Fahrudin; Hattab, Syahruddin; Chaeriah Ahsan, Sitti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this study is to find out, analyze, and study the implementation of the Pioneer Shipping Service Policy in Class II ports in Palu Bay, Central Sulawesi Province. Qualitative and descriptive research methods. The location of the research was carried out at the Municipal Office and Class II Port Authority of Palu Pantoloan Bay, with eight informants selected purposefully. The data collection is done through interviews, observations, and documentation. The data analysis techniques of interviews use Nvivo 12 software and are supported by interactive models from Miles, Huberman, and Saldana, data collection, data condensation, data display, and conclusion drawings. The results of the research showed that: (1) communication to socialize the maritime transportation services of pioneer ships in hammer bay ports is still not maximized; (2) resources in terms of human resources and means are optimum, but budget (financial) and Prasarana resources are not sufficient; (3) dispositions on implementation are well running in connection with the appointment of the Commitment Maker Office (PPK) including incentives; (4) bureaucratic structures are still ineffective in relation to the mechanisms of implementation of the marine transportation service of the pioneers that have not been followed up by creating a Standard Operation Procedures (SOPs) and on the execution of the established shipping route is not appropriate and the time of sail in 1 (one) voyage is too long. Conclusion Implementation of Pioneer Shipping Services Policy in Class II Ports of Palu Bay, Central Sulawesi Province, is not effective. The findings in this study require strengthening of the integrated monitoring and monitoring aspects explaining the final determination in the pioneering shipping services policy in the Class II ports of Hammer Bay.